Emergency Landing in Budapest. Hungarian Literature and SovietCulture Policy During „Bad Weather Conditions.” - Seres, Attila (Acta Scientiarum Socialium, 2016)
Emergency Landing in Budapest. Hungarian Literature and Soviet Culture Policy During „Bad Weather Conditions”. In October 1955 suddenly and quite unexpectedly two Soviet writers appeared in Budapest, who had to stay there for some days because of the emergency landing of their planes to Vienna and Tirana, respectively. One of them was Aleksandr Borisovich Chakovskiy (1913–1994), editor in chief of Inostrannaya Literatura, the Soviet world literature’s magazine, the other was the well-known Soviet author and essayist Ilya Grigoryevich Ehrenburg (1891–1967). It seemed a good occasion for the Hungarian party leadership to organize meetings with Hungarian writers and some main representatives of the cultural policy of the Hungarian Worker’s Party and make the political opposition of Hungarian writers face with the Soviet literary policy doctrines. The consequences of both Chakovsky’s and Ehrenburg’s several days stay in Budapest became a „case” in the Central Comittee of the Soviet Communist Party and made the party leadership orientate Soviet litterateurs regarding the official position on political movements of writers in the Socialist countries.